2018
DOI: 10.1111/2041-210x.13005
|View full text |Cite
|
Sign up to set email alerts
|

An automated barcode tracking system for behavioural studies in birds

Abstract: Recent advances in technology allow researchers to automate the measurement of animal behaviour. These methods have multiple advantages over direct observations and manual data input as they reduce bias related to human perception and fatigue, and deliver more extensive and complete datasets that enhance statistical power. One major challenge that automation can overcome is the observation of many individuals at once, enabling whole‐group or whole‐population tracking. We provide a detailed description of an au… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 51 publications
0
56
0
Order By: Relevance
“…Information about fine-scale associations within flocks would help to conclusively show that social interactions with future extra-pair mates differ from other close neighbours. To fully understand whether and how prior social associations affect mating patterns, studies using more advanced tracking technologies [64] are needed to capture finer-scale patterns of social preferences. Furthermore, studies examining how differences in winter social structure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Information about fine-scale associations within flocks would help to conclusively show that social interactions with future extra-pair mates differ from other close neighbours. To fully understand whether and how prior social associations affect mating patterns, studies using more advanced tracking technologies [64] are needed to capture finer-scale patterns of social preferences. Furthermore, studies examining how differences in winter social structure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, we still know relatively little about why stress appears to programme individuals to be more socially gregarious and less choosy. Captive experiments in which finer details about the directionality of inter-individual interactions can be captured, facilitated by recent innovations in long-term high-resolution tracking individuals [95], could provide new insights into the mechanisms-how do stressed individuals end up being more central and well-connected? A combination of new technology and methods, and additional targeted field studies, will hopefully allow us to determine whether the differences that have been observed are caused by the decisions of the stressed individuals themselves or the behaviour of others towards them.…”
Section: Discussionmentioning
confidence: 99%
“…After each swap, we recalculated the network, thus producing 10 000 random networks. Significance was calculated by comparing the observed coefficient value to the distribution of coefficient values from the randomized networks (following [59], see also [61]). For effects that were significant in Boogert et al [28], we used a one-tailed significance test, whereas we used a two-tailed test for effects that were not significant in Boogert et al [28].…”
Section: (D) Statistical Analysesmentioning
confidence: 99%
“…In addition to formalizing the analysis of social data, studies in the field of social network analysis have stimulated the development of tools and technologies for studying animals at fine scales over long periods of time. Approaches such as individual‐tracking using PIT tags (Farine & Sheldon, ), barcodes (Alarcon‐Nieto et al, ), proximity loggers (Ryder et al, ), and GPS tracking data (Kays et al, ), are facilitating a revolution in the resolution of data that can be collected on between‐individual interactions. When combined with long‐term studies, these will hopefully provide the data required to address these exciting new questions.…”
Section: Quantifying Selection Arising From the Social Environmentmentioning
confidence: 99%